Potential of Indonesian Plants as Polymicrobial Anti-Biofilm - Rafika Sari; Sylvia Utami Tunjung Pratiwi; Yosi Bayu Murti; Ema Damayanti (Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Biofilm infection occurs in 80% of chronic infections caused by 60% of biofilms from plankton cells and polymicrobial biofilms. Due to synergistic interactions between species, infections caused by polymicrobial biofilms are more virulent than monospecies biofilm infections. New anti-biofilm candidates are constantly being developed by tracing the content of active compounds from medicinal plants native to Indonesia. The need to find new plant sources that have the potential as anti-biofilms is increasingly needed along with increasing microbial resistance. Various studies show that active compounds that have anti-biofilm potential are polyphenols, quercetin, curcumin, gallic acid, and ferulic acid. The mechanism of action of anti-biofilms is through the prevention of attachment and formation of biofilms, inhibition of quorum sensing, and inhibition of gene expression in microbes.